ANALISIS PENGARUH TINGKAT INFLASI, TINGKAT SUKU BUNGA, DAN NILAI TUKAR TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA (BEI) PERIODE 2013-2015 - Primavistanti, Daniar; Sutanto, Aftoni (Universitas Ahmad Dahlan, 2016)
This research aimed to analyze and test the effect of inflation rates, interest rate and exchange rate on the stok price index at the stock exchange in 2013–2015. Independent variable used are inflation, interest rates, and exchange rates. While the dependent variable is the stock price index. The object of this research is in the market listed on the stock price index. The inflation rates, interest rates, and the exchange rate that are taken from Indonesian Bank. The analytical method used is the classic assumption test and regression test. Based on the survey result revealed that in partial inflation and the exchange rate does not significantaly influence the Stock Exchange Composite Index. While the variable interest rate significantly influence the Stock Exchange Composite Index. The test results simultaneosly show variable inflation, interest rates and exchange rates have an influence on the Stock Exchange Composite Index. The coefficient of determination was 28,3%.